Micromechanical analysis of sand production. (10th January 2019) - Garolera, Daniel; Carol, Ignacio; Papanastasiou, Panos
Summary: We present a micromechanical approach based on zero‐thickness interface elements for modelling advanced localization and cracking states of cemented granular materials, such as reservoir sandstones. The proposed methodology is capable of reproducing the complex behaviour of intergranular and intragranular localization, cracking, and fracturing of rock formation that leads to sanding in hydrocarbon production. The model is calibrated at the macroscale, using only a few physical parameters, by reproducing the typical behaviour of compression element tests. The model exhibits clear transition behaviour from brittle dilatant to ductile compactant behaviour with increasing confining stress. The methodology is implemented for sand production prediction analysis based on the simulation of 2D micromechanical models of hollow cylinder cross sections. The obtained results are compared well with published experimental data from hollow cylinder tests characterized by strong scale effect in the range of small perforations.